Iron deficiency and iron deficiency anemia in women - Coad, Jane; Pedley, Kevin (Scandinavian journal of clinical & laboratory investigation. Supplement, 2014)
Abstract Iron deficiency is one of the most common nutritional problems in the world and disproportionately affects women and children. Stages of iron deficiency can be characterized as mild deficiency where iron stores become depleted, marginal deficiency where the production of many iron-dependent proteins is compromised but hemoglobin levels are normal and iron deficiency anemia where synthesis of hemoglobin is decreased and oxygen transport to the tissues is reduced. Iron deficiency anemia is usually assessed by measuring hemoglobin levels but this approach lacks both specificity and sensitivity. Failure to identify and treat earlier stages of iron deficiency is concerning given the neurocognitive implications of iron deficiency without anemia. Most of the daily iron requirement is derived from recycling of senescent erythrocytes by macrophages; only 5-10 % comes from the diet. Iron absorption is affected by inhibitors and enhancers of iron absorption and by the physiological state. Inflammatory conditions, including obesity, can result in iron being retained in the enterocytes and macrophages causing hypoferremia as a strategic defense mechanism to restrict iron availability to pathogens. Premenopausal women usually have low iron status because of iron loss in menstrual blood. Conditions which further increase iron loss, compromise absorption or increase demand, such as frequent blood donation, gastrointestinal lesions, athletic activity and pregnancy, can exceed the capacity of the gastrointestinal tract to upregulate iron absorption. Women of reproductive age are at particularly high risk of iron deficiency and its consequences however there is a controversial argument that evolutionary pressures have resulted in an iron deficient phenotype which protects against infection.